Forced fluid removal in intensive care patients with acute kidney injury: The randomised FFAKI feasibility trial. Issue 7 (17th April 2018) - Berthelsen, R. E.; Perner, A.; Jensen, A. K.; Rasmussen, B. S.; Jensen, J. U.; Wiis, J.; Behzadi, M. T.; Bestle, M. H.
Abstract : Background: Accumulation of fluids is frequent in intensive care unit (ICU) patients with acute kidney injury and may be associated with increased mortality and decreased renal recovery. We present the results of a pilot trial assessing the feasibility of forced fluid removal in ICU patients with acute kidney injury and fluid accumulation of more than 10% ideal bodyweight. Methods: The FFAKI‐trial was a pilot trial of forced fluid removal vs standard care in adult ICU patients with moderate to high risk acute kidney injury and 10% fluid accumulation. Fluid removal was done with furosemide and/or continuous renal replacement therapy aiming at net negative fluid balance > 1 mL/kg ideal body weight/hour until cumulative fluid balance calculated from ICU admission reached less than 1000 mL. Results: After 20 months, we stopped the trial prematurely due to a low inclusion rate with 23 (2%) included patients out of the 1144 screened. Despite the reduced sample size, we observed a marked reduction in cumulative fluid balance 5 days after randomisation (mean difference −5814 mL, 95% CI −2063 to −9565, P  = .003) with forced fluid removal compared to standard care. While the trial was underpowered for clinical endpoints, no point estimates suggested harm from forced fluid removal. Conclusions: Forced fluid removal aiming at 1 mL/kg ideal body weight/hour may be an effective treatment of fluid accumulation in ICU patients with acute kidney injury. A definitive trial using our inclusion criteria seems less feasible based on our inclusion rate of only 2%.